PEMBERDAYAAN MASYARAKAT DI PERPUSTAKAAN BAHAGIA MENDAWAI KAMPUNG CAPING PONTIANAK - Ela Darma Sari; Atiqa Nur Latifa Hanum (Universitas Tanjungpura, 2022)
This research discusses Community Empowerment in The Bahagia Mendawai Library of Kampung Caping Pontianak. The purpose of this research is to find out the role of libraries in empowering the community as well as the obstacles and efforts made to overcome these obstacles. This study uses qualitative descriptive methods with data collection techniques namely observation, interview, and documentation. The number of informants in the study consisted of six sources. The results of this study show that the Bahagia Mendawai Library plays a role for community empowerment that focuses on community empowerment activities to increase reading interest and coaching activities for community welfare. For activities to increase reading interest, the Mendawai library has innovation activities such as literacy trails, reading carts and cyberliteration with the target of children of the village of the sea bansir. While library coaching activities have activities called creative classes with cooking class activities, waste processing, planting activities, making wedding souvenirs and making accessories for women. target community activities around the library. In the implementation of library activities have obstacles such as the difficulty of finding children in the location of activities. From these obstacles, the Mendawai library has an effort to overcome obstacles by collaborating on activities in order to attract visitors.